Effect of aging time on physicochemical properties of "Huangtan soy sauce" - YAO Jianhua, YU Wei, LI Jiajian, LUO Zhongying, FAN Kai, LI Xin (Zhongguo niangzao)
In this experiment, using the "Tou-you" and the "Er-you" of "Huangtan soy sauce" aged for 7 years, 4 years and 2 years as raw materials, the effects of aging time on the quality of "Yuan-you" were studied, and the quality difference between "Tou-you" and the "Er-you" were compared. The results showed that with the extension of aging time, the contents of amino acid nitrogen, soluble salt-free solids, total acid, free amino acid and color value increased, the contents of reducing sugar and sodium chloride of the "Tou-you" and the "Er-you" decreased. The contents of amino acid nitrogen, reducing sugar, soluble salt-free solids, total acid and free amino acids in the "Tou-you" were significantly higher than those in the "Er-you" (P<0.05). The amino acid nitrogen content of the "Tou-you" aged for 7 years was about 5.2 times that of the "Er-you" aged for 2 years. The analysis of electronic nose and electronic tongue showed that the contents of nitrogen oxides, sulfur compounds and alkanes in soy sauce were higher, among which the content of "Tou-you" aged for 7 years was the highest, and the richness of sourness, astringency, bitter aftertaste and umami gradually increased with the extension of aging time. In summary, prolonging the aging time could significantly improve the quality of "Yuan-you", and the quality of the "Tou-you" was higher than that of the "Er-you".